2021
DOI: 10.1002/ange.202016805
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Strain and Its Conformational Complexity Is a Major Factor in the Binding of Cyclic Dinucleotides to STING Protein

Abstract: STING (stimulator of interferon genes) is ak ey regulator of innate immunity that has recently been recognized as ap romising drug target. STING is activated by cyclic dinucleotides (CDNs) whiche ventually leads to expression of type Ii nterferons and other cytokines.F actors underlying the affinity of various CDN analogues are poorly understood. Herein, we correlate structural biology,isothermal calorimetry (ITC) and computational modeling to elucidate factors contributing to binding of six CDNs-three pairs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The same applies for hydrodynamic radii. Very small differences were observed between pK a s of ionogenic groups of the CDN diphosphorothioate (9) and its difluorinated derivatives (10)(11)(12). Their limiting mobilities and hydrodynamic radii were also similar.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The same applies for hydrodynamic radii. Very small differences were observed between pK a s of ionogenic groups of the CDN diphosphorothioate (9) and its difluorinated derivatives (10)(11)(12). Their limiting mobilities and hydrodynamic radii were also similar.…”
Section: Discussionmentioning
confidence: 85%
“…As such, the role of CDNs in defense against pathogens as well as sensing of tumor cells makes them important for understanding, and potentially for treatment, of a number of autoimmune diseases [3], cancers [4], and viral diseases [5,6], as well as having potential as adjuvants in vaccines [7]. Noticeably, one of the most intensively studied ligand-protein binding equilibria is the interaction of the STING (or its mutants) with various CDNs, including chemically modified nucleobases, phosphodiester linkages, or sugar units [8,9]. Of the particular interest is the 2′,3′-cyclic diadenosine diphosphorothioate (2′,3′-c-di-AMPS) compound, known also as ADURO-S100, which was evaluated in Phase I clinical study.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, only a few theoretical studies dealing with MD simulations of mutated STING have been reported to date. Notably, a study of the interaction of the agonist DMXAA on mouse STING and cyclic dinucleotide (CDN) screening studies are available in the literature. Very recently, MD simulations were performed on a wild-type STING model complexed with different CDNs, including cGAMP . The binding was shown to induce conformational reorganization, as also suggested by dynamic network and cross-correlation analyses.…”
Section: Introductionmentioning
confidence: 99%